IMPLEMENTING ARTIFICIAL INTELLIGENCE AS VIRTUAL ASSISTANT FOR MEDICAL DIAGNOSIS - Vianto, Vincent Octarian (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
Artificial intelligence (AI) is wide-ranging division of computer science concerned with building sharp machines competent of performing errands that frequently require human bits of knowledge. AI is an interest science with various approaches, but movements in machine learning and significant learning are making a worldview move in basically each division of the tech industry. AI can we implemented as virtual assistant to help patients to identify their illness and suggest whether the patient needs a medication or further diagnosis directly by doctors. Virtual assistant can reduce unnecessary physical meetings between doctors and patients, especially for infectious diseases such as COVID-19.